Association between Dietary Omega-3 Intake and Dry Eye Syndrome in Adults: A Cross-Sectional Study - Anisa Henintya Rizki Putri; Husnun Amalia (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Dry eye syndrome (DES) is a common ocular surface disorder that can impair visual function and quality of life, particularly among working-age adults. Although DES has a multifactorial etiology, nutritional factors, such as omega-3 fatty acid intake, have been suggested to modulate inflammation associated with the condition. This study aimed to investigate the association between dietary omega-3 intake and dry eye syndrome in adults. This cross-sectional analytical observational study included 88 participants aged 15-59 years. Participants were selected using consecutive non-random sampling and assessed with a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) to estimate omega-3 intake, while dry eye symptoms were evaluated using the Ocular Surface Disease Index (OSDI). Statistical analyses included chi-square and Fisher’s exact test. The results showed that 51.1% of the participants had insufficient omega-3 intake (<250 mg/day), and 29.5% experienced dry eye syndrome. No statistically significant association was found between sex or age and DES occurrence. However, a significant association was found between omega-3 intake and dry eye syndrome (p < 0.001), with individuals consuming insufficient omega-3 having a substantially higher risk of developing DES. These findings suggest that adequate omega-3 intake may play a protective role in dry eye syndrome. This study underscores the potential of dietary interventions as a strategy for preventing and managing DES.